Effectiveness of leaders' employee communication during organisational crisis: a perception of Malaysian crisis employees - Nagappan, Kalaivany; Ahmad, Abdul Mua'ti @ Zamri; Abdullah, Zulhamri (UPM Press, 2021)
Possibilities for occurrences of issues and conflicts due to the changes in the corporate environment have increased, thus demanding the leaders to be competent in controlling the crisis through effective communication. The role of internal stakeholders or employees has always been undervalued by both the industry leaders and scholars. Organisations in Malaysia especially, lack in crisis communication preparedness as many leaders do not come forward to acknowledge or face their crisis situation and many areas of crisis communication within local context are still being unexplored by the researchers especially from the employees’ perspectives. Thus, this study is designed to further contribute into finding the role of leaders in communicating effectively during an organisational crisis. The study is very much inductive where sense making theory form the foundation in guiding the research. Sense making takes place when the employees in the study confront their leaders regarding the crisis situation and the issues the employees face during the crisis. The research is a qualitative case study conducted among the employees of a local news media organisation which was going through a crisis and the researcher was an insider of the organisation. The media agency that covers broadcasting news went through both financial and management crisis affecting many of its employees. The selection of participants were done through purposive sampling. 10 employees of the said news media organisation with different demography were interviewed. Thematic analysis was applied to analyse the data. Categories, themes and constructs were identified and discussed. Members check, thick description and maximum variation sampling was used as a mean of establishing the trustworthiness of the study. The employees reported lack of information on cause of the crisis and the situation they were positioned. Formal communication such as meetings, emails and memos were rare. Clarity, consistency and credibility of crisis message were given least priority by their leaders. This study enables organisations to develop crisis communication plans that has clear guidelines in establishing communication system and platforms that prioritize employee communication and based on organization culture and context. The findings would assist to enhance the company communication policies and protocols as to be designed to protect the employees’ needs in the wake of a crisis.